Ellipsometry of thin films of biological objects under conditions of total internal reflection - Valeriy V. Yatsishen (Физика волновых процессов и радиотехнические системы, 2022)
An analysis of the ellipsometric parameters of the reflected light from the prism – test material – air system is carried out when circularly polarized light is incident on it under the conditions of the onset of the phenomenon of total internal reflection. At the onset of total internal reflection, the ellipsometry parameter Δ shows high variability with the angle of incidence, in contrast to the parameter r0. It is shown that TIR occurs when the angle of incidence is not equal to the critical angle of the adjacent media – for two different materials, these angles differ from each other. In the case of a film, the TIR phenomenon occurs at an angle equal to the critical angle at the prism-air interface and does not depend on the film material. The results obtained show the high efficiency of using the ellipsometric method together with circularly polarized incident radiation for diagnostics of thin films made of biological material.